1994
DOI: 10.1128/jvi.68.9.5925-5932.1994
|View full text |Cite
|
Sign up to set email alerts
|

Vitronectin receptor antibodies inhibit infection of HeLa and A549 cells by adenovirus type 12 but not by adenovirus type 2

Abstract: The penton base gene from adenovirus type 12 (Adl2) was sequenced and encodes a 497-residue polypeptide, 74 residues shorter than the penton base from Ad2. The Ad2 and Adl2 proteins are highly conserved at the aminoand carboxy-terminal ends but diverge radically in the central region, where 63 residues are missing from the Adl2 sequence. Conserved within this variable region is the sequence Arg-Gly-Asp (RGD), which, in the Ad2 penton base, binds to integrins in the target cell membrane, enhancing the rate or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Mean values of three independent determinations Ϯ the standard errors of the means are shown. (4,5,55,56), echoviruses (63,64), aphtoviruses (21), herpes simplex virus (72), adenovirus (1,26,70), and human immunodeficiency virus (65). Unfortunately, the wide distribution of the receptors and accessory factors, which is broader than the observed tropism of the viruses mediated by these receptors and factors, suggests that host cell restriction is also mediated by additional limiting processes that probably take place after virus binding and internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Mean values of three independent determinations Ϯ the standard errors of the means are shown. (4,5,55,56), echoviruses (63,64), aphtoviruses (21), herpes simplex virus (72), adenovirus (1,26,70), and human immunodeficiency virus (65). Unfortunately, the wide distribution of the receptors and accessory factors, which is broader than the observed tropism of the viruses mediated by these receptors and factors, suggests that host cell restriction is also mediated by additional limiting processes that probably take place after virus binding and internalization.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of a virus to replicate in different tissues raises questions about virus attachment and the role of the fiber protein. Various studies with the HAVs have shown that the fiber is responsible for initial attachment to the cellular receptor, which is followed by binding to cell surface integrins (43), a step mediated by a sequence in the penton base (1). The binding to integrins may be the common step in adenovirus infection (24), while the cellular receptors for the fiber may differ (5).…”
Section: Discussionmentioning
confidence: 99%
“…CAR mRNA is preferentially expressed in the heart, testis, prostate, and pancreas, which are not tissues targeted by enteric Ads infection. Moreover, the internalization of the majority of Ad serotypes is due to their interaction with integrins avh3 and avh5 via an RGD motif present in the virus penton base protein (Bai et al, 1994;Mathias et al, 1994;Wickham et al, 1993). However, Ad40 and Ad41 lack the RGD motif in their penton bases or fibers (Albinsson and Kidd, 1999).…”
Section: Introductionmentioning
confidence: 99%